Influence of Cardiologists’ Demographic Profile on Overall Satisfaction Towards Marketing Mix Strategies - Sultana, Jesmin; Saifuddin, Mohammad; Bhuiyan, Zakir Hossain (Dhaka University Journal of Pharmaceutical Sciences, 2022)
This study aims to investigate the influence of cardiologists’ demographic characteristics on their satisfaction towards marketing mix strategies (MMS) employed by pharmaceutical industries in Bangladesh. Cardiologists (156) were asked to rate the importance of variables of MMS indicating their degree of agreement with satisfaction statement using a 5-point Likert scale. The variables of marketing mix (4Ps) that can be ranked as top 5 out of 14 variables according to their Spearman correlation coefficients are - brand image (r = 0.532); selling skill of medical representatives (r = 0.507), place of retail pharmacy (r = 0.484), promotional policies (r = 0.476) and continuous medical education program for doctors (r = 0.345). Though the overall mean satisfaction score of females (M = 4.06, SD = 0.87) is higher than that of male (M=3.84, SD =1.02), the difference is not significant; p = 0.260, Cohen’s d = 0.217 showed the effect is small. Experience above 10 years was labeled as high (41%), otherwise low (59%). Experience had substantial influence on perceived satisfaction towards promotion. Finally, overall satisfaction scores varied based on academic qualification of cardiologists; p < 0.05, and Eta-squared = 0.068 implies medium effect. The highest overall satisfaction score was attained for D. Card and others (M = 4.32, SD = 0.82) and the lowest is for MD (M = 3.57, SD =10.9). Cardiologists’ satisfaction score towards product (the lowest is for MD and the highest is for D. Card and others); p < 0.05; Eta-squared = 0.05 (small effect) and promotion (the lowest is for MBBS and the highest is for D. Card and others) vary significantly according to their academic qualification, p < 0.05; Eta-squared = 0.095 implies medium effect. Dhaka Univ. J. Pharm. Sci. 21(2): 205-215, 2022 (December)